2010
DOI: 10.1007/s00268-010-0800-1
|View full text |Cite
|
Sign up to set email alerts
|

Chasing “Shadows”: Discovering the Subtleties of Sestamibi Scans to Facilitate Minimally Invasive Parathyroidectomy

Abstract: With careful preoperative re-review of a negative or indeterminate sestamibi scan and the identification of subtleties in patients with a negative preoperative US scan, a successful MIP can be performed 91% of the time with a 98% cure rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…These studies reported that surgeon interpretation and radiology experience increased the likelihood of localization [44,[45][46][47]. The authors recommend that sestamibi scans be reviewed by experienced parathyroid surgeons, rather than relying on radiological interpretation alone [45][46][47].…”
Section: Localization Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies reported that surgeon interpretation and radiology experience increased the likelihood of localization [44,[45][46][47]. The authors recommend that sestamibi scans be reviewed by experienced parathyroid surgeons, rather than relying on radiological interpretation alone [45][46][47].…”
Section: Localization Techniquesmentioning
confidence: 99%
“…Elevated levels of serum calcium and PTH are associated with a 95% risk of a diagnosis for classic PHPT; however, patients may have normal levels of phosphate, calcium or PTH. Serum calcium levels et al reported a sensitivity of 58.6% for nuclear medicine physicians, compared with 81.9% for both a surgeon and a nuclear medicine physician [47].…”
Section: Differential Diagnosis and Work-upmentioning
confidence: 99%
See 1 more Smart Citation
“…While we do not routinely use SUS, we do routinely analyze and interpret preoperative imaging with the radiology and nuclear medicine physicians. We have previously shown that when the surgeon and radiologist together carefully re-review preoperative sestamibi scans (initially called by the radiologists as being "negative" or "indeterminate"), subtleties can often be discovered that may change operative strategy from bilateral neck exploration to minimally invasive parathyroidectomy (MIP) in a substantial proportion of cases (63%) [7]. It worth noting that in such cases, MIP can be performed successfully 91% of the time with a cure rate of 98% [7].…”
mentioning
confidence: 99%
“…The two radio-pharmaceuticals used are 99m Tc-Sestamibi and 99m TcTetrofosmin. Despite its limitations and variable accuracy TS along with pre-operative ultrasound has an established role in centers which perform large volume parathyroid surgery (1,2). However there are technical and biological factors that affect the uptake of the 99m Tc in the parathyroid adenoma and potentially affect the sensitivity and specificity of scan.…”
Section: Introductionmentioning
confidence: 99%